(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides insights into the use of problem-based learning technologies in the formation of students’ cognitive skills in the teaching of natural sciences, the use of heuristic, research-based learning technologies in the organization of physics and chemistry lessons, and the organization of problem-based learning.